Examining Influential Elements Impacting Performance In Sustainable Manufacturing Within Malaysian Enterprise: A Conceptual Analysis - Ang, Hong Loong; Suddin Lada; Wang, Kehui; Chin, Jin Bui; Li, Xinyue (Penerbit Universiti Malaysia Sabah, 2024)
This study investigates the factors of sustainable manufacturing that affect the performance of Malaysian manufacturing enterprises. It focuses on sustainable innovation, quality, cost efficiency, delivery, and operational flexibility. By applying Dynamic Capabilities theory, the study aims to provide useful insights to Malaysian manufacturing companies. The major goal is to develop a conceptual framework for sustainable manufacturing that will improve organizational performance. It is important to emphasize that empirical validation is currently lacking in this study, necessitating additional research to examine the applicability of Dynamic Capabilities, sustainable innovation, and flexibility in predicting organizational performance. Future research should incorporate quantitative approaches and different samples to enhance the generalizability of the findings. This study emphasizes the critical roles of sustainable innovation and flexibility in influencing organizational performance, highlighting the importance of including these factors in sustainable manufacturing strategies. Furthermore, it provides stakeholders in manufacturing enterprises with insights to help them strengthen their strategic communication on the benefits of sustainable manufacturing. The study not only offers valuable information to policymakers, industry experts, and the academic community but also emphasizes the importance of conducting additional empirical research to examine and expand upon these conceptual insights.